PMO-173 District general hospital networks can provide safe and effective hepatitis C treatment: results of a 4-year audit. (28th May 2012) - Hydes, T; Allen, H; Al-Shamma, S; Hovell, C; Sharer, N; Williams, E
Abstract : Introduction: Chronic Hepatitis C (CHC) treatment is well described in the context of Randomised Controlled Trials (RCTs). 1 Whether these findings can be extrapolated to treatment programmes delivered by nurse specialists working in District General Hospitals (DGHs) is unclear. Methods: The Dorset Viral Hepatitis Network has a catchment area of 750 000 people. Patients are assessed and treated in three DGHs by a team of nurse specialists working under the supervision of four lead clinicians. Between January 2007 and January 2011 standard of care for CHC treatment was Ribavirin and Pegylated Interferon α2a given for 24 weeks (G2/3 patients) to 48 weeks (G1/4). A retrospective analysis of the network's reference database was undertaken focusing on treatment naïve patients. Results: In total 207 treatment naïve patients received antiviral therapy. Mean age at time of treatment was 43 years (20–66); 74% (154) were male and 67% (139) acquired CHC through injection drug use. G1 patients represented 49% (102) of the cohort; 3% (6) were Hepatitis B/HIV co-infected and 95% (196) were Caucasian. A clinical or histological diagnosis of cirrhosis was present in 8% (16). In total 12% (24) moved out of area or were lost to follow-up within 24 weeks of completing treatment. Based on intention to treat, Sustained Virological Response rates (undetectable HCV RNA in serum 24 weeks post treatment) were comparable to those derived from RCT 1 data (Abstract PMO-173 table 1 ). Non-response was observed in 11% (11/102), 5% (5/98) and 14% (1/7) of G1, G2/3 and G4 patients respectively. Breakthrough or relapse was observed in 18% (18/102), 13% (13/98) and 14% (1/7) of G1, G2/3 and G4 patients respectively. Overall 1% (3) of patients discontinued treatment as a result of a laboratory abnormality and 12% (24) because of other medical complications or side effect intolerance. These proportions are comparable to those observed in RCTs (p=0.735, p=0.146). Conclusion: Specialist nurses supported by a network of DGHs can deliver a high quality Hepatitis C service across a broad geographical area. These findings are encouraging when considering a move towards community based CHC management. Competing interests: None declared. Reference: 1. Fried MW, Shiffman ML, Reddy KR, et al. Peginterferon alfa-2a plus ribavirin for chronic hepatitis C virus infection. New Engl J Med 2002;347 :975–82.